Jan Brueghel and the senses of scale - Honig, Elizabeth Alice 1960- (The Pennsylvania State University Press, 2016)
"Examines the small-scale works of the Flemish painter Jan Brueghel the Elder, and the aesthetic and cognitive operation of smallness in art of the late sixteenth and early seventeenth centuries"...Provided by publisher